2021
DOI: 10.1007/s13555-021-00596-8
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity Profile of the Tyrosine Kinase 2 Inhibitor Deucravacitinib Compared with Janus Kinase 1/2/3 Inhibitors

Abstract: Introduction: Deucravacitinib, a novel, oral, selective inhibitor of tyrosine kinase 2 (TYK2) signaling, acts via an allosteric mechanism by binding to the enzyme's regulatory domain instead of the catalytic domain. This unique binding provides high functional selectivity for TYK2 versus the closely related Janus kinases (JAKs) 1/2/3. Deucravacitinib was efficacious in phase 2 and 3 psoriasis trials, without clinical or laboratory parameters indicative of JAK 1/2/3 inhibition being observed. This analysis comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 22 publications
2
69
0
2
Order By: Relevance
“…Therefore, due to safety concerns with JAK 1, 2 and 3 inhibitors, interest has shifted to more selective inhibition of TYK2. At clinically relevant doses and exposures, deucravacitinib demonstrates highly selective inhibition of TYK2 [30,34,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, due to safety concerns with JAK 1, 2 and 3 inhibitors, interest has shifted to more selective inhibition of TYK2. At clinically relevant doses and exposures, deucravacitinib demonstrates highly selective inhibition of TYK2 [30,34,36].…”
Section: Discussionmentioning
confidence: 99%
“…The use of deucravacitinib in psoriatic patients decreases IL-23 pathway biomarkers in lesional skin towards non-lesional levels and normalizes IFN and IL-12 pathway genes, without affecting JAK 1, 2 and 3 biomarkers. Through this mechanism of action, deucravacitinib blocks IL-12, IL-23 and type I interferon downstream signalling, without interfering with JAK2-dependent hematopoietic functions [17,36]. Preclinical studies initially showed its efficacy in mouse models with lupus erythematosus and inflammatory bowel disease [37][38][39].…”
Section: Deucravacitinibmentioning
confidence: 99%
“…This mode of binding, which differs from that of JAK1/2/3 inhibitors, is associated with the high selectivity of BMS-986165. 9 , 69 …”
Section: Tyk2 Inhibitors Progressmentioning
confidence: 99%
“…This mode of binding, which differs from that of JAK1/2/3 inhibitors, is associated with the high selectivity of BMS-986165. 9,69 In a phase 2 clinical trial, adults with moderate to severe plaque psoriasis were randomized into six groups. Patients received oral medication at 3 mg every other day, 3 mg once daily (QD), 3 mg twice daily (BID), 6 mg BID, 12 mg QD, or placebo.…”
Section: Bms-986165mentioning
confidence: 99%
“…Therefore, inhibition of each subtype of JAK can interfere with various downstream signaling pathways, acting as a powerful treatment for limiting inflammation in psoriasis [57]. Deucravacitinib (BMS-986165, Sotyktu; Bristol-Myers Squib) is a highly selective once-daily oral TYK2 inhibitor, recently approved by the FDA (9 September 2022) for the treatment of moderate-to-severe plaque psoriasis [49,58]. Avoiding the enzyme's catalytic domain, which is highly between JAKs, deucravacitinib instead binds to its regulatory/pseudokinase (JH2) domain, allowing for more potent blocking of downstream IL-12, IL-23, and type-1 interferon signaling [58].…”
Section: Janus Kinase Inhibitorsmentioning
confidence: 99%